Assessment of Pathogen Contamination in Food at Teaching Hospitals in Mashhad, Iran: A Cross‐Sectional Study - Mojtaba Raeisi; Fateme Asadi Touranlou; Golshan Shakeri; Maliheh Doustinouri; Arefeh Erfani; Asma Afshari; Mohammad Hashemi (Health Science Reports, 2026)
ABSTRACT Background and Aims Infectious diseases in hospitals pose a significant threat, with some linked to contaminated food. Food safety is a critical issue for hospital patients, particularly those with weakened immune systems. This study aimed to conduct the first comprehensive microbial evaluation of hospital catering across 12 teaching hospitals in Mashhad, Iran. Methods A total of 360 food samples from 10 distinct food categories (simple rice, mixed rice with meat or vegetables, barbecue chicken, kebab kubideh, chicken, fish, soup, stew, and raw vegetables) were analyzed. Integrated streaking culture and PCR techniques targeting the 16 s InvA , prfA , eaeA , groEL , and 16S rDNA genes were employed to confirm five key pathogens. Results The prevalence of pathogens was as follows: Salmonella spp. (8.3%), Listeria monocytogenes (5.8%), Escherichia coli O157:H7 (1.1%), Bacillus cereus (0.6%), and Clostridium perfringens (0.6%). Raw vegetables exhibited the highest contamination (5.70 ± 0.46 log CFU/g, with 6 samples exceeding Iranian National Standards), followed by grilled foods, indicating cross‐contamination risks. Overall, 16.4% of samples (59/360) failed microbial quality standards, highlighting significant safety concerns for vulnerable immunocompromised patients. Conclusion These findings highlight the urgent need for enhanced washing protocols for raw vegetables, adequate cooking temperatures, and staff training to ensure safe hospital catering.